Self-Confidence and Interpersonal Communication Anxiety among College Students in Makassar - Nurfitriany Fakhri; Intan Febriany Ayu Lestari; Ahmad Yasser Mansyur; Sahril Buchori (Sean Institute, 2023)
Interpersonal communication anxiety is a mental health issue that may be encountered by individuals, including those who are enrolled in academic institutions. Individuals who exhibit low levels of confidence and evaluate themselves unfavorably in social interactions may experience interpersonal communication anxiety directed towards themselves. The objective of this research is to establish a correlation between confidence and anxiety in interpersonal communication among college students residing in Makassar city. The present study employs quantitative methodologies. The present study employed an accidental sampling method, with a sample size of 470 participants (n = 470). The researcher utilized self-confidence and interpersonal communication anxiety scales that were compiled for the purposes of this study. The statistical analysis of the research data was conducted using the Spearman Test, utilizing the SPSS 22.0 software for Windows. The findings indicate that a statistically significant inverse correlation exists between self-assurance and anxiety related to interpersonal communication among undergraduate students residing in Makassar city (p=0.000, r=-0.156). This study found that the greater the level of self-confidence, the lower the level of interpersonal communication anxiety; conversely, the lower the level of self-confidence, the higher the level of interpersonal communication anxiety in Makassar city college students. The findings of this study may help students avoid more serious mental health issues by lowering their levels of worry about interpersonal communication.